Abandoned well CO2 leakage mitigation using biologically induced mineralization: current progress and future directions. Issue 1 (12th February 2013) - Cunningham, Alfred B.; Lauchnor, Ellen; Eldring, Joe; Esposito, Richard; Mitchell, Andrew C.; Gerlach, Robin; Phillips, Adrienne J.; Ebigbo, Anozie; Spangler, Lee H.
Abstract Methods of mitigating leakage or re‐plugging abandoned wells before exposure to CO2are of high potential interest to prevent leakage of CO2 injected for geologic carbon sequestration in depleted oil and gas reservoirs where large numbers of abandoned wells are often present. While CO2resistant cements and ultrafine cements are being developed, technologies that can be delivered via low viscosity fluids could have significant advantages including the ability to plug small aperture leaks such as fractures or delamination interfaces. Additionally there is the potential to plug rock formation pore space around the wellbore in particularly problematic situations. We are carrying out research on the use of microbial biofilms capable of inducing the precipitation of crystalline calcium carbonate using the process of ureolysis. This method has the potential to reduce well bore permeability, coat cement to reduce CO2–related corrosion, and lower the risk of unwanted upward CO2 migration. In this spotlight, we highlight research currently underway at the Center for Biofilm Engineering (CBE) at Montana State University (MSU) in the area of ureolytic biomineralization sealing for reducing CO2 leakage risk. This research program combines two novel core testing systems and a 3‐dimensional simulation model to investigate biomineralization under both radial and axial flow conditions and at temperatures and pressures which permit CO2 to exist in the supercritical state. This combination of modelling and experimentation is ultimately aimed at developing and verifying biomineralization sealing technologies and strategies which can successfully be applied at the field scale for carbon capture and geological storage (CCGS) projects. © 2013 Society of Chemical Industry and John Wiley & Sons, Ltd